2017
DOI: 10.1364/ol.42.001871
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-slow light propagation by self-induced transparency in ruby in the superhyperfine limit

Abstract: Self-induced transparency is reported for circularly polarized light in the R1(-3/2) line of a 30 ppm ruby (α-Al2O3:Cr3+) at 1.7 K in a magnetic field of B‖c=4.5  T. In such a field and temperature, a 30 ppm ruby is in the so-called superhyperfine limit resulting in a long phase memory time, TM=50  μs, and a thousand-fold slower pulse propagation velocity of ∼300  m/s was observed, compared to the ∼300  km/s measured in the first observation of self-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In contrast, we have recently reported slow and fast light effects based on transient spectral hole-burning in the R 1 -line at low temperatures [42,43]. We have also reported the generation of ultraslow solitons by self-induced transparency [44,45]. The latter could quantitatively be modeled by simulations applying the optical Bloch equations [44].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, we have recently reported slow and fast light effects based on transient spectral hole-burning in the R 1 -line at low temperatures [42,43]. We have also reported the generation of ultraslow solitons by self-induced transparency [44,45]. The latter could quantitatively be modeled by simulations applying the optical Bloch equations [44].…”
Section: Introductionmentioning
confidence: 93%
“…We have also reported the generation of ultraslow solitons by self-induced transparency [44,45]. The latter could quantitatively be modeled by simulations applying the optical Bloch equations [44]. For the hole-burning-caused slow light, the linear filter theory as presented in Refs.…”
Section: Introductionmentioning
confidence: 98%
“…In the following four decades, Szabo et al explored a wide range of subtle details in the spectroscopy of the R-lines [17][18][19][20]. In recent years, slow light effects based on spectral hole-burning have been reported [21] and SIT [22] has been re-examined, resulting in demonstrating solitons that propagate with a very low group velocity of ∼300 m s −1 . Very recently we have shown that electron spin polarization by optical pumping could make slow light in ruby slower, that is, this was an experiment where the propagation of light was controlled by two light pulses in the conditioning step [12].…”
Section: Introductionmentioning
confidence: 99%